CONDITIONAL RELEASE: POSSIBILITIES AND OBSTACLES IN SERBIA AND THE NETHERLANDS - Jan Hoekman; Gordana Krstić (Revija za kriminologiju i krivično pravo)
This paper analyses the concept of conditional release in the Netherlands and Serbia, to provide a comparative overview of the two legal systems, and to suggest how legal solutions could be improved. Conditional release is functionally correlated with imprisonment as the main criminal sanction, entailing the deprivation of liberty, whilest, it is also an alternative to imprisonment. It creates the possibility for the convicted person to be released from prison before they have fully served their sentence, provided that certain conditions are met. While serving the sentence, the convicted person is obliged to act upon the individual plan to rehabilitate, focus on work, and minimize the risk of reoffending. Since there are different categories of convicted persons in the penal environment, this paper will also examine whether all these categories of convicted persons deserve to be released on parole or whether perhaps conditional release is reserved only for privileged ones.